ALK Rearrangements Characterize 2 Distinct Types of Salivary Gland Carcinomas Clinicopathologic and Molecular Analysis of 4 Cases and Literature Review - Agaimy, Abbas; Baneckova, Martina; Ihrler, Stephan; Müller, Sarina Katrin; Franchi, Alessandro; Hartmann, Arndt; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2021)
The majority of salivary gland carcinomas are characterized by recurrent gene fusions that proved highly valuable diagnostically, but only rarely of therapeutic impact. Most of these fusion-positive carcinomas belong to the low-grade or intermediategrade biological category. To date, only 5 cases of salivary gland carcinomas carrying an oncogenic ALK fusion have been reported in 4 recent studies, but their phenotypic spectrum and their nosological classification remain uncharacterized. We herein describe in detail the clinicopathologic and molecular features of 4 ALK-fusion-positive salivary carcinomas and review previously reported cases to assess if they could be classified into a defined World Health Organization (WHO) category. Patients were 3 men and 1 woman aged from 67 to 79 years (median: 70 y). All tumors originated in the parotid gland. Their size ranged from 1.1 to 3 cm (mean, 2 cm). Three tumors were de novo high-grade salivary duct carcinomas (SDCs) and 1 was a low-grade intercalated-type intraductal carcinoma. Histologically, high-grade tumors were predominantly solid, composed of intimately admixed basal (CK5+, androgen-) and luminal (CK5-, androgen+) components. The remarkable basal component showed squamoid basophilic pattern imparting an adenosquamous-like appearance in all cases. Conventional apocrine intraductal high-grade carcinoma was noted in 1 case. Prominent intraductal growth of the solid basal component (highlighted by p63 staining) was seen in all cases. The tumor cells expressed CK7 (3/3), mammaglobin (3/3, 1 focal), GATA3 (3/3, 1 focal), variably CK5 (3/3), and focally the androgen receptor (1/3), but lacked expression of HER2/neu, SOX10, MUC4, TTF1, FS100, and Napsin A. The low-grade tumor showed classic histologic and immunophenotypic features of intercalated-type non-invasive intraductal carcinoma. Molecular profiling showed rearrangements involving exon 20 of ALK in all cases, confirmed by ALK immunohistochemistry (IHC and FISH). The fusion partner was EML4 (n= 2) and STRN (n= 1) in high-grade tumors and EML4 in the intraductal carcinoma. Two patients with high-grade tumors developed progressive disease (1 died at 9 mo; 1 alive under palliative therapy at 5 mo). This series and a review of 5 published cases indicate that ALK rearrangements characterize 2 distinct subsets of salivary gland carcinomas in the spectrum of high-grade androgen-poor, basal-like SDC (total reported: 5 cases) and low-grade intercalated-type intraductal carcinomas (4 cases). Given the therapeutic relevance of ALK fusions, inclusion of ALK IHC in any atypical-looking or androgen-poor SDC and in high-grade adenocarcinoma-not otherwise specified is recommended. Absence of aberrant ALK expression in genetically characterized secretory (n= 15) and intraductal (n= 9) carcinomas lacking ALK fusions underlines the value of ALK IHC as a diagnostic screening method for identifying potential cases.
CRIS-Team WoS Importer:2021-08-27